Artificial intelligence in synthetic chemistry: achievements and prospects. (December 2017) - Baskin, Igor I.; Madzhidov, Timur I.; Antipin, Igor S.; Varnek, Alexandre A.
Abstract : The review is devoted to the achievements in analysis of information on chemical reactions using machine learning methods. Four large areas that actively use these methods are outlined: computer-assisted planning of synthesis, analysis and visualization of chemical reaction data, prediction of the quantitative characteristics of reactions and computer-aided design of catalysts. The bibliography includes 346 references.